PENGARUH TEKNIK SIMULASI AUDIOVISUAL TABLETOP TERHADAP PENGETAHUAN REMAJA PMR TENTANG PENATALAKSANAAN KEGAWATDARURATAN BENCANA BANJIR - Windy Astuti Cahya Ningrum (IKesT Muhammadiyah Palembang, 2024)
Introduction: The high intensity of rainfall makes Indonesia a flood-prone area. Objective: To determine the effect of Tabletop Audiovisual Simulation Techniques on the Knowledge of PMR Adolescents on Emergency Management of Flood Disasters at SMPN 30 Palembang. Methods: The design of this study was a pre-experiment with a one group pretest posttest design without a control group design. The population in this study were students of SMPN 30 Palembang who were members of PMR with a sample of 30 respondents. The sampling technique used consecutive sampling which was carried out from January to June 2023. The research results were analyzed using the Wilcoxon test. Results: there is an effect of providing tabletop audiovisual simulations on the emergency management of flood disasters on the knowledge of PMR students at SMPN 30 Palembang (p value = 0.000). Conclusion: tabletop audiovisual simulation can increase knowledge about flood disaster emergency management. So that tabletop audiovisual simulations can be used as an effective method for increasing knowledge and preparedness for flood disaster management that is interesting and easy to understand.